Method for producing water-absorbing resin
The method enhances water-absorbing resin performance by incorporating a reactive polymer in a surface crosslinking reaction, improving liquid flow conductivity and absorption capacity while maintaining holding power, addressing colloid blocking and leakage issues.
Patent Information
- Application Number
- JP2023106112
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-06-28
AI Technical Summary
Conventional water-absorbing resins face challenges in maintaining high liquid flow conductivity and absorption capacity under pressure while preserving holding power, often leading to colloid blocking and liquid leakage issues.
A method involving a reactive polymer in a surface crosslinking reaction, using a water-absorbing resin composition that undergoes free radical polymerization, followed by surface crosslinking with a reactive polymer containing polyethylene and polyacrylic acid segments, to enhance liquid flow conductivity and absorption capacity.
The method improves liquid flow conductivity and absorption capacity under pressure, maintaining high holding power and reducing leakage, with the water-absorbing resin exhibiting properties like liquid permeability and retention capacity.
Smart Images

Figure 2025005769000001 
Figure 2025005769000002 
Figure 2025005769000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a water-absorbent resin, and more particularly to a method for producing a water-absorbent resin having excellent liquid flow conductivity. [Background technology]
[0002] Water-absorbent resins are used in a wide range of applications, such as water retention agents in agriculture or horticulture, anti-dew coagulants in building materials, materials for removing water from petroleum, waterproof outer coating agents in cables, and personal hygiene products (e.g., paper diapers, feminine hygiene products, disposable towels, etc.), among which paper diapers are the main application.
[0003] The absorption performance of a paper diaper is determined by the absorption speed, absorption amount, and smoothness. In recent years, paper diapers have been made thinner by reducing the amount of pulp (hydrophilic fiber) used and increasing the amount of water-absorbing resin used, thereby increasing the proportion of water-absorbing resin in the absorbent structure of the paper diaper. However, if the amount of hydrophilic fiber used is reduced, the water storage space becomes smaller in a short time, the liquid permeation speed becomes slow, and the liquid leaks before being absorbed. In addition to having an excellent absorption speed, the water-absorbing resin needs to have high permeability to liquid. If the liquid permeability is poor, the water-absorbing resin blocks the gaps between particles when absorbing liquid, causing a colloid blocking phenomenon, causing the liquid to flow out of the absorbent body of the paper diaper, thereby reducing the absorption performance of the paper diaper.
[0004] Therefore, improving the absorption rate and permeability of water-absorbent resins is currently one of the main focuses of research in this field. In the conventional method, surface modification with polyvalent metal cations or aluminum dihydroxyacetate can be used to improve the liquid flow conductivity of water-absorbent resins. In order to improve the liquid permeability of water-absorbent resins, thermoplastic polymers such as polyethylene and polypropylene can be used in the heat treatment process, or an amino group-containing azo compound can be added as a blowing agent to the acid group-containing monomer aqueous solution. In addition, by adding an encapsulated blowing agent or a water-soluble alkoxysilane compound to the acid group-containing monomer aqueous solution, the manufactured water-absorbent resin can have an excellent absorption rate and high colloidal stability. Furthermore, it is known that the diffusibility and liquid permeability of the water-absorbent resin after absorbing a liquid can be improved by mixing a water-soluble polyvalent metal powder, an adhesive, and a water-absorbent resin.
[0005] In addition, in order to achieve the effects of improving the absorption rate, improving the colloid strength, improving the anti-caking property and the liquid permeability, the conventional water-absorbing resin is subjected to a surface cross-linking treatment to form further cross-links on the surface of the water-absorbing resin. For example, conventional methods include dispersing the water-absorbing resin and a cross-linking agent in an organic solvent and performing a surface cross-linking treatment, mixing an inorganic powder into the water-absorbing resin and performing a cross-linking treatment, adding a cross-linking agent and then performing a steam treatment, performing a surface treatment using an organic solvent, water and a polyhydric alcohol, and performing a surface treatment using an organic solvent, water and an ether-based compound. However, although the conventional surface treatment methods can improve the absorption rate and the water absorption capacity under pressure, there is a risk that the retention force of the water-absorbing resin is significantly reduced, which reduces the practical effect.
[0006] In view of this, it is necessary to provide a water-absorbent resin that can improve both the liquid flow conductivity and the water absorption capacity under pressure and maintain a high retention force, and a method for producing the same. Summary of the Invention
[0007] One aspect of the present invention provides a method for preparing a water-absorbent resin that involves a reactive polymer in a surface cross-linking reaction to improve the liquid flow conductivity of the resulting water-absorbent resin.
[0008] Another aspect of the present invention provides a water-absorbing resin produced by the above aspect.
[0009] According to one aspect of the present invention, there is provided a method for producing a water absorbent resin, comprising the steps of: subjecting a water absorbent resin composition, which comprises an aqueous unsaturated monomer solution, a polymerization initiator, and a free radical polymerization crosslinking agent, to a free radical polymerization reaction to obtain a colloidal gel; subsequently, pulverizing and sieving the colloidal gel to obtain a plurality of water absorbent resin particles; and subjecting the water absorbent resin particles to a surface crosslinking reaction with a reactive polymer comprising a surface crosslinking agent, a polyethylene segment, and a polyacrylic acid segment to obtain a water absorbent resin.
[0010] According to one embodiment of the present invention, the reaction polymer is an ethylene acrylic polymer, which comprises a polyethylene segment represented by the following formula (1) and a polyacrylic acid segment represented by the following formula (2): [ka] M is a hydrogen atom, a Group IA element, or a Group IIA element. When the ethylene acrylic polymer is 100 wt%, the polyethylene segment is 80 wt% to 99 wt%, and the polyacrylic acid segment is 1 wt% to 20 wt%.
[0011] According to one embodiment of the present invention, the weight of the polyethylene segment in the reaction polymer is 100 wt %, and the weight of the polyacrylic acid segment is 8 wt % to 20 wt %.
[0012] According to one embodiment of the present invention, assuming that the weight of the water-absorbent resin particles is 100 wt %, the amount of the reactive polymer added is 0.01 wt % to 10 wt %.
[0013] According to another aspect of the present invention, there is provided a water-absorbent resin which is produced by the above method and has a T20 value of 180 seconds or less.
[0014] According to one embodiment of the present invention, the liquid flow conductivity of the water absorbent resin is 30×10 -7 cm 3 -s / g or more.
[0015] According to an embodiment of the present invention, the retention capacity of said water absorbent resin is greater than 20g / g.
[0016] The water absorbent resin and the manufacturing method thereof of the present invention have an effect of improving the liquid flow conductivity and the water absorption capacity under pressure of the water absorbent resin by involving a reactive polymer in a surface cross-linking reaction, and can maintain the retention power of the water absorbent resin at a high level, and therefore have practical utility. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] As used herein, "around," "about," "approximately," or "substantially" generally refers to within 20%, or within 10%, or within 5% of a numerical value or range.
[0018] As described above, the present invention provides a water absorbent resin which has an effect of improving the liquid flow conductivity and the water absorption capacity under pressure of a water absorbent resin by involving a reactive polymer in a surface cross-linking reaction, and can maintain high retentivity of the water absorbent resin, and is therefore practical, and a method for producing the same.
[0019] The method for producing a water-absorbing resin provided by the present invention includes a step of subjecting a water-absorbing resin composition to a free radical polymerization reaction to obtain a colloidal gel. In some embodiments, the water-absorbing resin composition includes an aqueous solution of an unsaturated monomer, a polymerization initiator, and a free radical polymerization crosslinker.
[0020] In some embodiments, the unsaturated monomer aqueous solution in the water absorbent resin composition includes an acid group monomer having an unsaturated double bond, such as acrylic acid. In some embodiments, the unsaturated monomer aqueous solution may be methacrylic acid, 2-acrylamido-2-methylpropanesulfonic acid, malic acid (cis-butenyl acid), cis-butenyl acid anhydride, fumaric acid (trans-butenyl acid), and trans-butenyl acid anhydride. The unsaturated monomer aqueous solution may include one type of monomer, but is not limited thereto, and two or more of the above monomer aqueous solutions may be selected.
[0021] In some embodiments, the concentration of the unsaturated monomer aqueous solution may be 20wt%-55wt%, preferably 30wt%-45wt%, but is not limited thereto. Generally, when the concentration of the acid group monomer aqueous solution is 20wt%-55wt%, the viscosity of the product after polymerization is appropriate, the machining is easy, and the reaction heat during the free radical polymerization reaction is easy to control.
[0022] In other embodiments, other hydrophilic monomers having unsaturated double bonds, such as acrylamide, methacrylamide, 2-carboxyethyl acrylate, 2-carboxyethyl methacrylate, methyl acrylate, ethyl acrylate, dimethylamine acrylamide, and trimethylamine chloride, may be selectively added. However, the amount of the hydrophilic monomer added should not impair the physical properties (e.g., retention and absorption speed) of the water absorbent resin.
[0023] In some embodiments, the acid group monomer aqueous solution may be directly polymerized, or may be partially neutralized with a neutralizing agent to make the acid group monomer aqueous solution neutral or weakly acidic, and then polymerized. In these embodiments, the neutralizing agent includes hydroxide or carbonate compounds of alkali metals or alkaline earth metals (e.g., sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate), amine compounds, and combinations thereof. In some embodiments, the neutralization concentration of the acid group monomer aqueous solution is 45 mol% to 85 mol%. When the neutralization concentration of the acid group monomer aqueous solution is in the above-mentioned range, the acid group monomer aqueous solution has a pH suitable for free radical polymerization reaction, and can reduce damage caused by accidental contact with the human body. As a supplementary explanation, the neutralization concentration in this specification is defined as the ratio of the moles of the basic solution to the moles of the acid group monomer aqueous solution, and may be the percentage of the acid groups in the acid group monomer aqueous solution that are neutralized.
[0024] In some embodiments, the pH value of the acid group monomer aqueous solution is 5.5 or more, preferably 5.5 to 7.0, and more preferably 5.5 to 6.5. When the pH of the acid group monomer aqueous solution is 5.5 to 7.0, a large amount of unreacted monomer is unlikely to remain in the aqueous solution after polymerization, and the water absorbent resin produced subsequently has good physical properties and a large absorption capacity.
[0025] In some embodiments, a water-soluble polymer may be selectively added to the water-absorbent resin composition to reduce manufacturing costs. In some embodiments, the water-soluble polymer includes partially or completely saponified polyvinyl alcohol, polyethylene glycol, polyacrylic acid, polyacrylamide, starch or starch derivatives (e.g., methyl cellulose, methyl cellulose acrylate, ethyl cellulose, etc.), and preferably, starch and partially or completely saponified polyvinyl alcohol are used alone or in combination. In the above embodiments, the molecular weight of the water-soluble polymer is not limited, and the amount of the water-soluble polymer added is generally 0 wt% to 20 wt%, preferably 0 wt% to 10 wt%, and more preferably 0 wt% to 5 wt%, assuming that the amount of the unsaturated monomer aqueous solution used is 100 wt%, as a rule, so as not to deteriorate the physical properties of the water-absorbent resin.
[0026] The prepolymerization reaction starts with the generation of radicals due to the decomposition of the polymerization initiator. In some embodiments, the amount of the polymerization initiator is 0.001wt% to 10wt%, preferably 0.1wt% to 5wt%, when the amount of the unsaturated monomer aqueous solution is 100wt%. When the amount of the polymerization initiator is within the above range, the speed of the free radical polymerization reaction is appropriate, it is economically beneficial, the reaction heat is easily controlled, and the formation of colloidal solids due to excessive polymerization can be avoided.
[0027] In some embodiments, the polymerization initiator includes a thermal decomposition initiator, a redox initiator, and a combination thereof. In some embodiments, the thermal decomposition initiator includes a peroxide [hydrogen peroxide, di-tert-butyl peroxide, peroxide amide or persulfate (including ammonium salt and alkali metal salt)], and an azo compound [e.g., 2,2-azobis(2-amidinopropane) dihydrochloride, 2,2-azobis(N,N-dimethyleneisobutylamidine) dihydrochloride]. In some embodiments, the redox initiator includes an acid sulfite, ascorbic acid, or a ferrous salt. The polymerization initiator is preferably a combination of a thermal decomposition initiator and a redox initiator, which reacts with the redox initiator to generate free radicals, which transfer to the monomer to initiate the polymerization reaction, and the large amount of heat released by the polymerization reaction increases the temperature of the reaction system. When the reaction system reaches a certain temperature, the thermal decomposition initiator can be further decomposed to make the polymerization reaction more complete, thus avoiding excess residual unreacted monomer.
[0028] The free radical polymerization crosslinking agent in the water absorbent resin composition can provide the water absorbent resin composition with an appropriate degree of crosslinking, and can improve the processability of the water absorbent resin composition after polymerization reaction. In some embodiments, the free radical polymerization crosslinking agent may be selected from compounds containing two or more unsaturated double bonds, such as N,N-bis(2-propenyl)amine, N,N-methylenebisacryloylamine, N,N-methylenebismethacryloylamine, propylene acrylate, ethylene glycol diacrylate, polyethylene glycol diacrylate, ethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, glycerin trimethacrylate, triacrylate or trimethacrylate obtained by adding ethylene oxide to glycerin, trimethylolpropane trimethacrylate, trimethylolpropane triacrylate, N,N,N-tris(2-propenyl)amine, ethylene glycol diacrylate, polyoxyethylene triacrylate, diethyl polyoxyethylene triacrylate, dipropylene triglycol, etc. In some embodiments, the free radical polymerization reactive crosslinker may be selected from compounds containing two or more epoxy groups, such as sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, diglycerol polyglycidyl ether, etc. The free radical polymerization reactive crosslinkers may be used alone or in combination of two or more.
[0029] In some embodiments, the amount of the free radical polymerization crosslinking agent is 0.001wt%-5wt%, preferably 0.01wt%-3wt%, when the amount of the acid group monomer aqueous solution is 100wt%. When the amount of the free radical polymerization crosslinking agent is within the above range, the viscosity of the polymer aqueous solution after the reaction is appropriate, it is easy to machine, and the absorption capacity of the water absorbent resin produced later is large, that is, the performance of the water absorbent resin is good.
[0030] In some embodiments, the free radical polymerization reaction may be carried out in a batch reactor or a conveyorized reactor.
[0031] In some embodiments, the colloidal gel may be selectively pulverized in a pulverizer to a particle size of 20 mm or less, preferably 10 mm or less, followed by a sieving step. In some embodiments, the sieving step is to select colloidal gel with a particle size of 2.0 mm or less, preferably 0.05 mm to 1.50 mm, and then return the colloidal gel with a particle size of more than 2.0 mm to the reactor for another pulverization. In order to avoid a large amount of fine powder being generated in the subsequent process, and to have good thermal conductivity and to avoid a high amount of residual monomer in the finished product, it is necessary to control the particle size within the above range. Generally, the narrower the particle size distribution of the colloidal gel, the better the physical properties and the more favorable the subsequent drying process.
[0032] In some embodiments, the colloidal gel may be optionally subjected to a drying process before carrying out subsequent operations. In some embodiments, the drying process is carried out at a temperature of 100° C. to 180° C. If the drying process is carried out in the aforementioned temperature range, the drying time can be effectively controlled, and the crosslinking degree can be effectively controlled to avoid a large amount of residual unreacted monomer.
[0033] Next, the method for producing the water-absorbent resin includes a step of crushing and sieving the colloidal gel to obtain water-absorbent resin particles. In some embodiments, the particle size of the water-absorbent resin particles is selected to be 0.06 mm to 1.00 mm, preferably 0.10 mm to 0.85 mm. By controlling the particle size of the water-absorbent resin particles to the above-mentioned range, the amount of fine powder in the finished product can be reduced, and the absorption performance of the water-absorbent resin can be improved. Similarly, the narrower the size distribution of the water-absorbent resin particles, the better the physical properties.
[0034] Then, the water-absorbent resin particles are surface-crosslinked with a surface crosslinking agent and a reactive polymer to obtain a water-absorbent resin. Since the water-absorbent resin is a hydrophilic polymer that is insoluble and has a uniform crosslinked structure inside the resin, it is necessary to further crosslink the surface of the resin in order to improve properties such as absorption speed, colloid strength, anti-caking property, and liquid permeability. The surface crosslinking reaction is carried out with a surface crosslinking agent having a functional group that can react with an acid group. In addition, in the present invention, a reactive polymer, for example an ionomer, is added to further increase the liquid flow conductivity of the produced water-absorbent resin, and the surface crosslinking reaction is carried out together.
[0035] In some embodiments, the surface cross-linking agent includes a polyol, a polyamine, a compound having two or more epoxy groups, and an alkylene carbonate, the polyol can be, for example, glycerol, ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, and propylene glycol, the polyamine can be, for example, ethylenediamine, diethylenediamine, and triethylenediamine, and the compound containing an epoxy group can be, for example, sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, ethylene glycol, propylene glycol, and the like. The alkylene carbonate may be, for example, ethylene glycol carbonate, 4-methyl-1,3-dioxolan-2-one, 4,5-dimethyl-1,3-dioxolan-2-one, 4,4-dimethyl-1,3-dioxolan-2-one, 4-ethyl-1,3-dioxolan-2-one, 1,3-dioxan-2-one, 4,6-dimethyl-1,3-dioxan-2-one, and 1,3-dioxepan-2-one. The reaction may be carried out using a single surface crosslinking agent or a combination of two or more types. Depending on the surface crosslinking agent selected, the surface crosslinking agent may be added directly, or may be added after preparing an aqueous solution or a hydrophilic organic solution. Hydrophilic organic solvents include, but are not limited to, methanol, ethanol, propanol, isobutanol, acetone, methyl ether, ethyl ether, and the like.
[0036] In some embodiments, the amount of the surface cross-linking agent added is 0.001wt% to 10wt%, preferably 0.005wt% to 5wt%, when the amount of the water absorbent resin particles used is 100wt%. When the amount of the surface cross-linking agent added is within the above-mentioned range, the water absorbent resin surface can have a cross-linked structure, thereby obtaining good absorption performance.
[0037] In order to effectively achieve the effects of the present invention, it is necessary to uniformly mix the water-absorbing resin and the reactive polymer, and therefore it is necessary to use a mixing device with high mixing effect. In some embodiments, the mixing device may be a V-type mixer, a column mixer, a high-speed stirring mixer, a spiral mixer, a flow mixer, a double-arm kneader, a double-arm cone mixer, a screw mixer, an internal mixer, a grinding kneader, a rotary mixer, or a screw extruder.
[0038] The ionomer is a polymer that contains repeating units of ionic units within a polymer of electrically neutral repeating units, and the ionic groups are actually part of the polymer backbone. In some embodiments, the ionic groups may be, for example, carboxylic acid groups. In these embodiments, the ionomer may be an ethylene-acrylic acid copolymer (EAA), which is a compound that includes a polyethylene segment of the following formula (1) and a polypropylene segment of the following formula (2): [ka] M is a hydrogen atom, a Group IA element (e.g., lithium, sodium, or potassium), or a Group IIA element (e.g., calcium or magnesium). In this embodiment, the ethylene acrylic polymer is 100 wt%, the polyethylene segment is 80 wt% to 99 wt%, and the polyacrylic acid segment is 1 wt% to 20 wt%.
[0039] In another embodiment, the ionomer may be an ethylene acrylic compound represented by formula (3): [ka] M is a hydrogen atom, a Group IA element (e.g., lithium, sodium, or potassium), or a Group IIA element (e.g., calcium or magnesium). In some embodiments, M is preferably a Group IA element.
[0040] In some embodiments, in the ethylene acrylic compound, the weight of the polyethylene segment (i.e., formula (1)) is 100wt%, and the weight of the polyacrylic acid segment (i.e., formula (2)) is 8wt% to 20wt%. In the ethylene acrylic compound, the polyethylene segment is a hydrophobic group and the polyacrylic acid segment is a hydrophilic group, so it is easy to absorb water. Therefore, if there are too many polyethylene segments (for example, if the weight of the polyacrylic acid segment is 8wt% or less), the absorption ability of the water absorbent resin decreases, and conversely, if there are too many polyacrylic acid segments (for example, if the weight of the polyacrylic acid segment is more than 20wt%), the ionomer itself absorbs moisture in the air and forms aggregates, so the mixing effect with the water absorbent resin particles decreases, and the expected effect of the present invention cannot be achieved.
[0041] In some embodiments, the amount of reactive polymer added is 0.01wt% to 10% when the weight of the water absorbent resin particles is 100wt%. Only when the amount of reactive polymer added is within the above range, the effect of improving the absorption capacity (e.g., water absorption capacity under pressure) of the water absorbent resin can be achieved.
[0042] In some embodiments where the ionomer is an ethylene acrylic compound, the surface cross-linking reaction includes heat treatment at a temperature of 150° C. to 210° C. By heat treatment at the aforementioned temperature, the ethylene acrylic compound can be completely melted, and a high quality water absorbent resin, i.e., a water absorbent resin with high water absorption capacity, can be obtained.
[0043] As described above, the present invention can produce a water-absorbent resin having a saline flow conductivity (SFC), and the liquid flow conductivity can be used to evaluate the permeability of a liquid. When the liquid permeability of a water-absorbent resin is high, the problems of rewetting of the absorbent body, reduction in smoothness, and leakage can be reduced. The liquid flow conductivity indicates that the water-absorbent resin that has absorbed a liquid has liquid permeability at high pressure, and when the liquid reenters the absorbent body, the liquid is likely to diffuse through the water-absorbent resin that has already absorbed the liquid to other water-absorbent resins that have not absorbed the liquid. The liquid flow conductivity of the water-absorbent resin of the present invention is 30×10 -7 cm 3 -s / g or more, preferably 40×10 -7 cm 3 -s / g or more.
[0044] Furthermore, the water-absorbent resin must have a good centrifuge retention capacity (CRC) and absorption against pressure (AAP) so that the pressure applied to the absorbent from the outside after absorbing the liquid does not damage it or affect its liquid absorption capacity. In some embodiments, the water-absorbent resin of the present invention has a centrifuge retention capacity of 20 g / g or more, preferably 25 g / g or more. In some examples, the water-absorbent resin of the present invention has an absorption capacity under pressure of more than 15 g / g, preferably more than 20 g / g, more preferably more than 23 g / g.
[0045] The ability of a dried water absorbent resin to absorb liquid when it starts to come into contact with the liquid may be expressed by the T20 value. A low T20 value of the water absorbent resin indicates that the dried water absorbent resin is more likely to absorb liquid. The T20 value of the water absorbent resin of the present invention is 180 seconds or less, preferably 160 seconds or less. As a supplementary explanation, the T20 value is defined as the time required for 1 gram of the water absorbent resin to absorb 20 grams of saline and 0.01 wt% aqueous solution of alcohol ethoxy compound under a pressure of 0.3 psi, where the alcohol ethoxy compound has 12 to 14 carbon atoms. In some embodiments, the T20 value of the water absorbent resin of the present invention is less than 180 seconds, preferably less than 160 seconds. The water absorbent resin of the present invention has both a low T20 value and a high liquid flow conductivity, and can reduce the amount of rewetting of the absorbent body and improve the smoothness of the paper diaper.
[0046] The absorbent body is formed into a sheet using the water-absorbent resin and hydrophilic fibers of the present invention. When actually used, the absorbent body may be placed on a polyethylene (PE) film that is not permeable to liquids, and a nonwoven fabric that is permeable to liquids may be used as a surface layer, or the water-absorbent resin may be fixed to a pulp fiber material (airlaid) and / or a nonwoven fabric. The pulp fiber may be crushed wood pulp, crosslinked cellulose fiber, cotton, wool, vinyl acetate fiber, etc. In general, assuming that the absorbent body is 100 wt%, the content of the water-absorbent resin (also called the core concentration) in the absorbent body is 20 wt% or more and 100 wt% or less, preferably 40 wt% or more and 100 wt% or less, and more preferably 50 wt% or more and 100 wt% or less. If a water-absorbent resin with such a high core concentration is used, the effect of the present invention can be further achieved. In general, the basis weight (weight per unit area) of the absorbent body is 0.01 g / cm 2 ~0.30g / cm 2 and the thickness of the absorber is 30 mm or less.
[0047] The application of the present invention will be described below using several examples, which are not intended to limit the present invention, and those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention. Preparation of reactive polymer Manufacturing Example 1
[0048] Take 1180g of ethylene acrylic compound (CAS NO. 9010-86-0, purchased from Aldrich-Sigma, containing 18wt% polyacrylic acid segment), 118g of sodium hydroxide, and 5g of pure water, and mix them in a Banbury mixer at a temperature of 150℃ for 30 minutes to obtain an ethylene acrylic compound (A) with neutral sodium ions. Manufacturing Examples 2-3
[0049] Repeat Preparation Example 1, the difference from Preparation Example 1 is that the ethylene acrylic compound in Preparation Example 2 contains 15wt% polyacrylic acid segment (CAS NO.9010-77-9, purchased from Aldrich-Sigma, contains 15wt% polyacrylic acid segment), and in Preparation Example 3, 172g magnesium hydroxide is used instead of sodium hydroxide to prepare the ethylene acrylic compound (B) having neutralized sodium ion and the ethylene acrylic compound (C) having neutralized magnesium ion, respectively. Manufacturing Examples 4-5
[0050] Preparation Example 1 was repeated, with the difference being that in Preparation Example 4, Escor containing 10 wt % polyacrylic acid segments was used. TM 5080, and in Example 5, Escor containing 7.5 wt % polyacrylic acid segment. TM The ethylene acrylic compound (D) and (E) having neutral sodium ions were prepared using ethylene acrylic compound (5020) (purchased from Exxon). Manufacture of water-absorbent resin Example 1
[0051] 503.12g of 48wt% sodium hydroxide aqueous solution was gradually added to a 2000cc Erlenmeyer flask containing 621.03g of acrylic acid and 670.74g of water, the sodium hydroxide / acrylic acid drop ratio was set to the range of 0.85-0.95, the drop time was set to 2 hours, and the temperature of the neutralization reaction system in the flask was maintained within the range of 15℃-40℃ to obtain an unsaturated monomer aqueous solution with a monomer concentration of 42wt%, in which 70mol% of acrylic acid was partially neutralized to sodium acrylate and the pH value was 5.69.
[0052] Next, 1.36 g of N,N'-methylenebisacrylamide (free radical polymerization reaction crosslinking agent) is added to the unsaturated monomer aqueous solution, and the temperature is maintained at about 20°C. Then, 0.35 g of hydrogen peroxide solution, 4.15 g of sodium hydrogen sulfite, and 4.15 g of ammonium persulfate are added as polymerization reaction initiators to carry out a free radical polymerization reaction.
[0053] The colloidal gel obtained by the reaction is pulverized with a cutter mill, and colloidal gel particles with a particle size of 2 mm or less are selected. Next, the colloidal gel is dried at a temperature of 130°C for 2 hours. The particles are further selected using a sieve with a uniform particle size of 0.1 mm to 0.85 mm to obtain water-absorbent resin particles.
[0054] Next, 2.5 g of a surface crosslinking agent, which is an aqueous solution of ethylene glycol, aluminum sulfate, and water in a volume ratio of 1:0.5:2, is added to 200 g of the obtained water absorbent resin particles, and 0.1 g of an ethylene acrylic compound (A) having a neutral sodium ion is added, and the mixture is heat-treated at a temperature of 160°C for 1 hour. After cooling, a water absorbent resin can be obtained. Examples 2 to 6
[0055] The water absorbent resins of Examples 2 to 6 are manufactured by the same process as Example 1. The difference is that the amount of ethylene acrylic compound (A) used in Example 2 is 1.0 g, 0.1 g of ethylene acrylic compound (B) is used in Example 3, 0.1 g of ethylene acrylic compound (C) is used in Example 4, 0.1 g of ethylene acrylic compound (D) is used in Example 5, and 4.63 g of polyethylene glycol 600-diacrylate (UM82-080, manufactured by Nissho Kako Co., Ltd.) is used as a free radical polymerization reaction crosslinking agent instead of N,N'-methylenebispropyleneamine in Example 6. Comparative Examples 1 to 6
[0056] The water absorbent resins of Comparative Examples 1 to 6 are manufactured by the same process as that of Example 1. The differences are that in Comparative Example 1, a non-neutralized ethylene acrylic compound (CAS NO. 9010-86-0, purchased from Aldrich-Sigma, containing 18 wt% polyacrylic acid segment) is used instead of the ethylene acrylic compound (A) having neutralized sodium ions, in Comparative Example 2, 0.1 g of ethylene acrylic compound (E) is used, in Comparative Example 3, no ethylene acrylic compound is added, in Comparative Example 4, 5 g of ethylene acrylic compound (E) is used, in Comparative Example 5, heat treatment is performed at a temperature of 140°C, and in Comparative Example 6, heat treatment is performed at a temperature of 250°C. Evaluation method
[0057] In order to evaluate the properties of the water-absorbent resin of the present invention, the physical properties are analyzed by the following test methods, and unless otherwise specified, all of the following measurements are performed under the conditions of room temperature of 23±2° C. and relative humidity of 45±10%. The water-absorbent resin needs to be thoroughly mixed before analysis. holding power
[0058] Centrifuge Retention Capacity (CRC) is tested according to the test method ERT441.3(10) specified by the European Disposables and Nonwovens Association (EDANA). The results of the retention capacity test for the water-absorbent resins are shown in Table 1. Water absorption rate under pressure
[0059] Absorption against pressure (AAP) is tested according to the test method ERT442.3(10) specified by EDANA, and is tested for absorption against 0.9% sodium chloride solution at a pressure of 4.9 kPa for 60 minutes. The test results of the absorption against pressure of the water absorbent resin are shown in Table 1. Liquid Flow Conductivity
[0060] Saline flow conductivity (SFC, unit: 10 -7 cm 3 The flow conductivity of the water absorbent resin is measured and calculated according to the method described in U.S. Patent 5,562,646, specifically, by placing the water absorbent resin in Jayco synthetic urine solution for 60 minutes and then measuring the flow conductivity of a 0.118M sodium chloride aqueous solution under a pressure of 0.3 psi. The flow conductivity of the water absorbent resin is shown in Table 1. T20 Value
[0061] The T20 value (unit: seconds) was measured and calculated according to the method described in U.S. Patent 9,285,302, which is the time required for 1 gram of water absorbent resin to absorb 20 grams of saline and 0.01 wt% aqueous solution of alcohol ethoxy compound under a pressure of 0.3 psi, where the alcohol ethoxy compound has 12-14 carbon atoms. The average results of three repeated tests are shown in Table 1.
[0062] [Table 1] Fabrication of absorber
[0063] Using an absorbent molding machine, 10.0 grams of absorbent resin and 10.0 grams of crushed wood pulp are mixed and molded, the molding mesh is a 400 mesh (38 μm) wire mesh, and the absorbent area is 160 square centimeters (8 cm x 20 cm). The molded absorbent is placed on a polyethylene film, and then a nonwoven fabric is placed on it. Next, the absorbent is pressed for 5 minutes with a pressure of 18.39 kPa (area 160 square centimeters, weight 30 kg), and the periphery is glued with white adhesive to obtain a test absorbent. Examples 7 to 12 and Comparative Examples 7 to 12
[0064] In Examples 7 to 12, absorbents were prepared by the above method using the water-absorbent resins of Examples 1 to 6, respectively, and in Comparative Examples 7 to 12, absorbents were prepared by the above method using the water-absorbent resins of Comparative Examples 1 to 6, respectively. The basis weights and thicknesses of the absorbents are shown in Table 2. Rewetting performance of absorbent body
[0065] The lower the rewet amount (i.e., smoothness) of the absorbent, the better the urine resistance of the water-absorbent resin. The test method is to place a weight of 4.8 kPa (area 160 square centimeters, weight 7.8 kg) on the absorbent prepared in the above Examples 7 to 12 and Comparative Examples 7 to 12, drop 180 mL of synthetic urine (Jayco synthetic urine described in U.S. Patent Publication No. 20040106745) at the center point in three separate times (30 minutes apart each time), and remove the weight from the absorbent 30 minutes after the drop is completed. Then, 30 sheets of filter paper (8 cm x 20 cm) whose total weight W1 has been measured in advance are placed on the absorbent, and a 4.8 kPa weight is immediately placed on the absorbent for 5 minutes to allow the filter paper to absorb the rewet liquid. Then, the weight W2 of the 30 sheets of filter paper is measured. The rewet amount of the synthetic urine of the absorbent is (W2-W1). The test results are shown in Table 2.
[0066] [Table 2]
[0067] According to the above test results, in Examples 1 to 6, compared with Comparative Examples 1 to 6, a water-absorbent resin having both high liquid flow conductivity and low T20 value can be obtained by involving an ethylene acrylic compound having a specific amount and neutral metal ions in a surface crosslinking reaction. In other words, the water-absorbent resins of Examples 1 to 6 not only have excellent liquid flow conductivity, but also have good liquid diffusibility and conduction ability in a dry state. In addition, according to Examples 7 to 12, the absorbent bodies made of the water-absorbent resins of Examples 1 to 6 have a liquid rewet amount lower than 3.0 g, which is obviously lower than the liquid rewet amounts of Comparative Examples 7 to 12, which indicates that they are also excellent in smoothness.
[0068] Therefore, by applying the method for producing a water absorbent resin according to the present invention and involving a reactive polymer in a surface cross-linking reaction of water absorbent resin particles, it is possible to effectively improve the liquid flow conductivity and liquid diffusibility in a dry state of the produced water absorbent resin, and also to maintain high retention power of the water absorbent resin, thereby providing practicality.
[0069] The present invention has been disclosed above based on the embodiments, but it is not limited to the present invention, and a person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention, and therefore the protection scope of the present invention is based on that defined in the appended claims.
Claims
1. A step of subjecting a water absorbent resin composition comprising an unsaturated monomer aqueous solution, a polymerization initiator, and a free radical polymerization reaction crosslinking agent to a free radical polymerization reaction to obtain a colloidal gel; pulverizing and sieving the colloidal gel to obtain a plurality of water-absorbent resin particles; A step of subjecting the water-absorbent resin particles to a surface cross-linking reaction with a surface cross-linking agent and a reactive polymer containing a polyethylene segment and a polyacrylic acid segment to obtain a water-absorbent resin; A method for producing a water-absorbing resin comprising the steps of:
2. The reaction polymer is an ethylene acrylic polymer, and the ethylene acrylic polymer contains the polyethylene segment represented by the following formula (1) and the polyacrylic acid segment represented by the following formula (2), 【Chemistry 1】 The method for producing a water-absorbing resin according to claim 1, wherein M is a hydrogen atom, an IA group element, or an IIA group element, and the ethylene acrylic polymer is 100 wt %, the polyethylene segment is 80 wt % to 99 wt %, and the polyacrylic acid segment is 1 wt % to 20 wt %.
3. 2. The method for producing a water-absorbent resin according to claim 1, wherein the weight of the polyethylene segment in the reactive polymer is 100 wt %, and the weight of the polyacrylic acid segment is 8 wt % to 20 wt %.
4. 2. The method for producing an absorbent resin according to claim 1, wherein the amount of the reactive polymer added is 0.01 wt % to 10 wt %, assuming that the weight of the water-absorbent resin particles is 100 wt %.
5. The method for producing a water-absorbent resin according to claim 1, wherein the water-absorbent resin has a T20 value of 180 seconds or less.
6. The liquid flow conductivity of the water absorbent resin is 30×10 -7 cm 3 The method for producing a water-absorbing resin according to claim 1, wherein the water-absorbing resin has a viscosity of -s / g or more
7. The method for producing a water-absorbing resin according to claim 1, wherein the water-absorbing resin has a retention force of more than 20 g / g.
Citation Information
Patent Citations
Surface cross-linked super absorbent resin and method for preparing same
EP3235856A1
Super absorbent polymer with high permeability
JP2007510045A
Thermoplastic coated superabsorbent polymer composition
JP2009519356A
Superabsorbent polymer having improved odor prevention performance and manufacturing method therefor
JP2015168824A
Water-absorptive resin particles and absorber and absorptive article containing the same
JP2017206646A